Pharmaceutical Proteins in Plants: A Strategic Genetic Engineering Approach for the Production of Tuberculosis Antigens - Frutos, Roger; Denise, Hubert; Vivares, Christian; Neuhaus, Jean-Marc; Vitale, Sandro; Pedrazzini, Emmanuela; Ma, Julian; Dix, Phil; Gray, John; Pezzotti, Mario; Conrad, Udo; Robinson, David (My University, 2008)
Tuberculosis (TB) is a re-emerging disease that is considered a major human health priority as well as an important disease of livestock. TB is also a zoonosis, and Mycobacterium tuberculosis and M. bovis, the human and bovine causative agents, respectively, are very closely related. Protection against TB is essentially achieved through vaccination with the Bacille Calmetle-Guerin (BCG) strain of M. bovis. Protection is, however, incomplete, and novel improved vaccines are currently under investigation. Production of protective antigens in transgenic plants, or "pharming," is a promising emerging approach, and a zoonosis-like TB is a good model for investigating the potential of this approach. Pharma-Planta, a European Commission-funded project and consortium, was set up to address this topic, within which a component is aimed at assessing the production efficacy and stability of the TB antigens in different compartments of the plant cell. This article is meant to introduce this promising approach for veterinary medicine by describing the ongoing project and its specific genetic engineering strategy.
Keywords: tuberculosis; plant biotechnology; vaccines; pharming; Pharma-Planta